1990
DOI: 10.1111/j.1439-0396.1990.tb00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen zum Einfluß von Fett‐ und Stärkezulagen auf den mikrobiellen Stoffwechsel im Pansensimulationssystem RUSITEC

Abstract: Zusammenfassung Es wurden zweifaktorielle Untersuchungen zum Einfluß von Stärke‐ und Fettzulagen auf den mikrobiellen Stoffwechsel im Pansensimulationssystem RUSITEC durchgeführt. Dazu wurde einer Grundration aus Heu und Konzentrat stufenweise native Weizenstärke und tierisches Mischfett zugelegt. Stärkezulagen senkten die Abbauraten von Rohfett, Rohprotein und Gerüstsubstanzen. Die Methanproduktion wurde nicht beeinflußt, die Ammoniakspiegel sanken. Die VFA‐Produktionsraten stiegen nur bei niedriger, nicht ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…A similar observation was made by Gerson et al (1985), who found that the in vitro rates of lipolysis and biohydrogenation were reduced when a portion of fibre in the diet of sheep was replaced by starch. More recently, the inhibitory effect of starch supplementation on lipolysis was confirmed in experiments using the rumen simulation technique (RUSITEC) (Abel et al, 1990).…”
Section: Introductionmentioning
confidence: 82%
“…A similar observation was made by Gerson et al (1985), who found that the in vitro rates of lipolysis and biohydrogenation were reduced when a portion of fibre in the diet of sheep was replaced by starch. More recently, the inhibitory effect of starch supplementation on lipolysis was confirmed in experiments using the rumen simulation technique (RUSITEC) (Abel et al, 1990).…”
Section: Introductionmentioning
confidence: 82%
“…1016/j.livprodsci.2005.11.012 (e.g., Machmü ller et al, 1998;Fievez et al, 2003). These studies showed that fat supplementation may be associated with a reduction in ruminal fibre degradation and sometimes even organic matter (OM) degradation, and, as fat is not fermentable, less truly fermentable OM which is important for microbial protein synthesis (Abel et al, 1990). This could result in a lower ruminal N utilisation and higher excretion of readily volatile urinary N at the expense of more stable faecal N. On the other hand, the altered digesta composition, when feeding fat-supplemented diets, might affect fermentation processes in manure (e.g., urease activity) as well.…”
Section: Introductionmentioning
confidence: 96%